2009
DOI: 10.1007/s00213-009-1562-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of GABAA receptors in the acute and chronic effects of ethanol: a decade of progress

Abstract: The past decade has brought many advances in our understanding of GABA A receptor-mediated ethanol action in the central nervous system. We now know that specific GABA A receptor subtypes are sensitive to ethanol at doses attained during social drinking while other subtypes respond to ethanol at doses attained by severe intoxication. Furthermore, ethanol increases GABAergic neurotransmission through indirect effects, including the elevation of endogenous GABAergic neuroactive steroids, presynaptic release of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
393
1
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(412 citation statements)
references
References 364 publications
(451 reference statements)
12
393
1
6
Order By: Relevance
“…Extrasynaptic GABA A receptors typically contain alpha 4 and alpha 6 subunits, whereas intrasynaptic GABA A receptors typically contain alpha 1-3 subunits (reviewed in ref. 31). During early phase withdrawal, physiological GABAergic disruptions lead to a transient increase in total numbers of GABA A receptors because extrasynaptic GABA A receptors remain elevated and the synaptic GABA A receptors are being recruited.…”
Section: Discussionmentioning
confidence: 99%
“…Extrasynaptic GABA A receptors typically contain alpha 4 and alpha 6 subunits, whereas intrasynaptic GABA A receptors typically contain alpha 1-3 subunits (reviewed in ref. 31). During early phase withdrawal, physiological GABAergic disruptions lead to a transient increase in total numbers of GABA A receptors because extrasynaptic GABA A receptors remain elevated and the synaptic GABA A receptors are being recruited.…”
Section: Discussionmentioning
confidence: 99%
“…GABA is the major inhibitory neurotransmitter in the central nervous system (CNS) and binds GABA A receptors that are a family of chloride ion channels that predominately mediate rapid inhibitory neurotransmission throughout the CNS (Kumar et al, 2009); activation of GABA A receptors by GABA results in an influx of chloride ions, which hyperpolarizes the membrane leading to neuronal inhibition. Moreover, GABA A receptors are heteromeric protein complexes consisting of several homologous membrane-spanning glycoprotein subunits that generate various subunit compositions and may account for variable sensitivity to modulatory drugs such as benzodiazepines, barbiturates, neuroactive steroids, ethanol, and general anesthetics (Olsen and Sieghart, 2009).…”
Section: Gaba As a Therapeutic Target For Addictionmentioning
confidence: 99%
“…As for the action of ethanol in the central nervous system, some in vitro brain slice studies have shown that ethanol facilitates the release of neurotransmitters such as c-aminobutyric acid (GABA), dopamine, serotonin, and opioids, whereas it inhibits glutamate activity, resulting in alterations in behavior [1]. Ethanol has been shown to be anxiolytic and sedative-hypnotic, as well as impairing cognition and motor coordination, through the enhancement of GABA release [17]. The effects of ethanol on pain perception, however, are controversial.…”
Section: Introductionmentioning
confidence: 99%